Lessons learned from implementing a virtual flipped classroom during COVID-19: An autoethnography (Journal of Applied Learning and Teaching, 2022)
The virtual flipped classroom has become a common practice in higher education during the COVID-19 pandemic. I used autoethnographic research to explore my personal teaching strategies and the challenges encountered while implementing a virtual flipped classroom during remote teaching in a higher education institution in Oman. A thematic analysis of the autoethnography account and interviews with two university teachers identified three themes: benefits of the virtual flipped classroom, challenges of the virtual flipped classroom and strategies for implementing the virtual flipped classroom. A framework for implementing this classroom style is proposed to guide higher education instructors when employing a virtual flipped classroom.